Desenho experimental para determinar o efeito do tamanho do pellet de catalisadores bimetálicos de Cu-Ni na reacção de deslocamento de agua] [Diseño experimental para determinar el efecto del tamaño del pellet de catalizadores bimetálicos Cu-Ni en la reacción de desplazamiento de agua (2018)
Bimetallic Cu-Ni catalysts were synthesized with molar ratio 2-1 in cylindrical activated carbon pellets of different diameters (0.2 cm, 0.3 cm, and 0.4 cm) and length (0.4 cm and 0.6 cm). They were evaluated in the water gas shift reaction at 330 °C and atmospheric pressure. An experimental design was developed to evaluate the effect of variables, diameter and length of the pellets, over carbon monoxide conversion. The importance of the main factors and their interactions were examined by analysis of variance (ANOVA). The results showed that both diameter and length of the pellets had significant effect on carbon monoxide conversion. The results of the catalytic activity indicated that up to 96% CO conversion was obtained at the optimum characteristic of the pellets, diameter of 0.2 cm and length of 0.6 cm. © 2018, Universidad Nacional de Colombia. All rights reserved.